(untitled) (Quinto Sol, 2019)
This article analyzes legal proceedings initiated by military defeats: the trial against Manuel Belgrano for his actions in Paraguay, the trial of residence to Juan José Castelli to evaluate his carrying out as representative of Provisional Government Junta and the lawsuit against Antonio González Balcarce after the disaster of Huaqui. Expeditions to Paraguay and Alto Perú were the first sent by the Junta of Buenos Aires to ensure the obedience of two key jurisdictions of Viceroyalty of Río de la Plata. After the failure of the campaigns, the revolutionary government prosecuted political and military leaders in order to neutralize openly oppositions and tepid adherences. In addition to this intention, the trials show the tensions that the war caused between military and political duties and responsibilities.